Melacak Akar Pers Islam - sheiful yazan (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2004)
Genealogy theory should be very useful for planning blue print framework to analyse strength, weakness, challenge, and oppttunity of Islamic mass media today. Writer tries to dig mass media values growth in Islam since Rasulullah period, This atticle addressed as early discourse about mass media theory in Islam